MIGRATORY GAME BIRDS AS A SOURCE OF PUBLIC EXPOSURE FROM THE FUKUSHIMA NUCLEAR POWER PLANT ACCIDENT - I. P. Stamat (Радиационная гигиена)
This article examines assessments of the impact of the Fukushima nuclear power plant accident on exposure of the Russian Federation population related to the seasonal migration of game birds. Intake of artificial radionuclides with meat of migratory game birds is shown to be one of the major pathways for the population exposure in the Far Eastern region of the country.